2021
DOI: 10.2196/22505
|View full text |Cite
|
Sign up to set email alerts
|

Initiatives, Concepts, and Implementation Practices of FAIR (Findable, Accessible, Interoperable, and Reusable) Data Principles in Health Data Stewardship Practice: Protocol for a Scoping Review

Abstract: Background Data stewardship is an essential driver of research and clinical practice. Data collection, storage, access, sharing, and analytics are dependent on the proper and consistent use of data management principles among the investigators. Since 2016, the FAIR (findable, accessible, interoperable, and reusable) guiding principles for research data management have been resonating in scientific communities. Enabling data to be findable, accessible, interoperable, and reusable is currently believ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Bioinformatics and biology as a whole have been early adopters of FAIR, and data management systems like the FAIRDOMHub [ 35 ] aid the creation of fair scientific data. In addition, the biomedical and health domains recently started to investigate FAIRification approaches [ 36–39 ].…”
Section: Interoperability Through Standards’ Implementation In Tools ...mentioning
confidence: 99%
“…Bioinformatics and biology as a whole have been early adopters of FAIR, and data management systems like the FAIRDOMHub [ 35 ] aid the creation of fair scientific data. In addition, the biomedical and health domains recently started to investigate FAIRification approaches [ 36–39 ].…”
Section: Interoperability Through Standards’ Implementation In Tools ...mentioning
confidence: 99%
“…FAIR (findable, accessible, interoperable and reusable) health data principles, initiatives, implementation practices, and lessons learned in the FAIRification process can meaningfully support both evidence based clinical practice and research transparency [ 8 ]. Data driven policy relies on the creation of universal guidelines for the architecture of strong health information systems which should include citizen associations in their governance structure, as is the case of the French Health Data Hub [ 9 ] at the national level or sought by regional projects, such as TEHDAS (Towards European Health Data Space).…”
Section: Resultsmentioning
confidence: 99%
“…FAIR is the combination of different small practices that make the data easier to find, easier to understand, less likely to be lost, and more likely to be usable during the project time and years later [16]. FAIR principles [11] are guidelines for data management and stewardship that are valid for both machines and humans: Findable: (meta)data should be discoverable, identifiable and searchable via the assignment of metadata and unique identifiers.…”
Section: Fair and Beyondmentioning
confidence: 99%
“…Article 5(1)(c) of the European Union's General Data Protection Regulation (GDPR) requires that personal data should be limited to only what is necessary to the purposes for which the data is processed [29]. Linking back to the discussion of FAIR, we note that in [5,16], authors suggested that FAIR data and metadata can facilitate compliance with data minimization principle since FAIR principles allow for an assessment of which data to reuse.…”
Section: Data Minimizationmentioning
confidence: 99%